The WORC Index and Predicting Treatment Failure in Patients Undergoing Primary Arthroscopic Rotator Cuff Repair. Issue 7 (29th July 2019) - Herring, Matthew J.; White, Melissa; Braman, Jonathan P.
Background: Rotator cuff tears are common injuries that are reliably treated with arthroscopic repair, producing good to excellent results. The Western Ontario Rotator Cuff (WORC) index is a validated disease-specific instrument used to assess patient outcomes; however, no study to date has correlated WORC index with treatment failure. Purpose: To evaluate the WORC index as a predictor for successful treatment in arthroscopic rotator cuff repair. An additional purpose was to identify patient and tear characteristics associated with risk of treatment failure. Study Design: Case-control study; Level of evidence, 3. Methods: This study reviewed a total of 500 patients who underwent arthroscopic rotator cuff repair with a minimum of 2-year follow-up. Patient charts were reviewed for treatment failures, defined as persistent or recurrent shoulder pain or weakness, leading to further workup and identification of a failure to heal or recurrent tear by magnetic resonance imaging. Patient demographic and comorbidity data were gathered and correlated with risk of failure. All patients completed WORC questionnaires, and scores were correlated with risk of treatment failure. Results: There were 28 (5.6%) treatment failures at a median 28 weeks (SD, 42 weeks) postoperatively. Patients claiming workers' compensation were 3.21 times more likely (odds ratio; P = .018) to fail treatment. Posterior interval tears (those including infraspinatus) were 3.14 times more likely ( P = .01) to fail than anterior interval tears. Tear size was associated with treatment failure; the odds of failure was 3.24 for a 2-tendon tear and 5.83 for a 3-tendon tear ( P = .03). Tears involving the nondominant arm were associated with an increased risk of failure by a factor of 3.04 (95% CI, 1.01-9.11; P = .047). A WORC score ≥80 was associated with a 95% probability of treatment success at 1 year. Conclusion: After arthroscopic rotator cuff repair, patients with WORC scores ≥80 at 1 year have a 95% probability of successful treatment and likely do not benefit from continued follow-up visits. Furthermore, several risk factors were identified that may influence outcomes after rotator cuff repair, including workers' compensation, location of tear, tear size, and hand dominance.